On the property (db) for continuous function spaces - Render, Hermann (Topology and its applications, 1999)
It is shown that the space C( X) of all continuous real-valued functions with the compact-open topology has the property (db) iff X is a μ-space and a τα-space. As a consequence C( X) has the property (db) iff C( X) is Baire-like answering a question in the literature. Generalizations to the topology of bounded convergence are given.